A novel parC mutation potentiating fluoroquinolone resistance in Klebsiella pneumoniae and Escherichia coli clinical isolates - Marwa Atef Yakout; Ghada Hani Ali (Journal of Infection in Developing Countries)
Introduction: Resistance to fluoroquinolones is mainly due to point mutations that gave rise to amino acid substitutions in the quinolone resistance-determining regions of either gyrA or parC genes, which may be augmented by plasmid mediated resistance. Accordingly, the main aim of the study was to investigate the mutations in gyrA and parC genes as well as the qnrA and qnrB genes acquisition.